(untitled) (Torani Journal of Fisheries and Marine Science, 2019)
Rabbitfish (Siganus canaliculatus) are found in seagrass beds so that they have the potential to be cultivated in the ecosystem. Cultivation activities require appropriate environmental / land requirements and support to be able to live and develop optimally. This study aims to analyze: (1) Suitability of rabbitfish cultivation land in seagrass ecosystem, (2) The carrying capacity of the land for rabbitfish cultivation in the seagrass ecosystem. This research was carried out in the coastal area of Barru Regency in March-April 2017. This study uses a method with the Remote Sensing Technology and Geographic Information Systems (GIS) approach. The types of data collected are oceanographic oceanic parameters consisting of physical factors (temperature, depth, current velocity, and turbidity), and chemical factors (salinity, pH and DO). The results of the study showed that the waters area was suitable ± 135.76 ha. Results estimation of the carrying capacity/capacity of the waters for rabbitfish cultivation with an area of about 81.46 ha or around 407,300 cultivation units or 5000 units / ha (assuming 1 unit of cultivation = 2 m2 (0,0002 ha). Keywords: land suitability, rabbitfish, carrying capacity